Аналіз сучасних НВЧ-установок для передпосівної обробки насіння сільськогосподарських культур - Чміль, А.І.; Лазарюк, К.О. (Енергетика і автоматика, 2017)
ANALYSIS OF CURRENT MIVROWAVE UNITS FOR PRESOWING SEED CROPS A. Chmil, K. Lazariuk Annotation. A literary and overview Patent electromagnetic microwave facilities offered by Ukrainian and foreign companies for pre-treatment of crop seeds. Keywords: ultrahigh frequency electromagnetic field, seeds, microwave installation, Pre-cultivation. Due to the constant rise in prices for pesticides and the costs of their production, transportation, there is a need to reduce the material and energy costs for processing presowing seed crops. One of the effective methods to solve this problem is the use of physical methods of seed treatment, namely the use of high frequency electromagnetic field (EMF SHF). The use of microwave systems in agriculture over the past decade, rapidly increased opportunities through effective rapid heating, sterilization, drying. The main objective of the intended processing of microwave energy EMF is to promote growth processes in the seeds, the destruction of pathogenic microorganisms and production of environmentally friendly products. The purpose of research - overview of microwave equipment and technologies intended for pre-treatment of crop seeds. Materials and methods of research. The electromagnetic field of ultrahigh frequency penetrates and acts quickly and evenly in the material. In contrast material that contains water in its composition wet-strength exposed to heat and can completely get rid of the water. After processing in microwave installation structure is not damaged seeds, nutrients are not lost. An important advantage of microwave systems is the lack of thermal inertia that can be almost instantaneous and turn off heat effects on seed processed. This allows you to maintain high accuracy regulation of pre-treatment of seeds. Efficiency works (COP) conversion of EMF microwave to heat almost close to 100%. Heat loss in the channels that carry energy, virtually zero, making the walls of chambers and waveguides are almost cold, which creates comfort conditions for staff. Currently Ukrainian and foreign scientists performing research work on processing seeds of various crops EMF microwave. The results showed positive results. The main physical factors influence the seed is heating temperature, which depends on the strength of electromagnetic fields and microwave processing time, storage time for planting, seeding and other (external factors). Many researchers have noted a steady increase in the yield of seeds processed in the microwave installation. This is because of improved crop quality (increasing similarity, vigor). The use of microwave systems due primarily to savings in energy, time and effective preplans tillage stimulation and disinfecting seed. Findings So literary patent examination has shown that the use of UHF - energy in agriculture has been successfully applied to improve the quality of seeds sown, disinfecting it, reduce energy consumption, environmentally friendly method of cultivation, as well as significantly reduce the duration of processing. Prospects for the wider use of high frequency electromagnetic field associated with the development and introduction of microwave - plants of new generation. Therefore, you should develop a microwave - setting that would meet the required parameters and modes should investigate electro physical exposure to EMF microwave on crop seeds for future development of microwave - setting that most would fully meet the requirements of agricultural production.